PENGEMBANGAN MAJALAH SEKOLAH VIRTUAL UNTUK MENINGKATKAN LITERASI PESERTA DIDIK DI KOTA DEPOK - Ananda, Refisa; Supratmi, Nunung; Syafruddin, Syafruddin (STKIP Pesisir Selatan, 2022)
Theschool'svirtualmagazineprovidesanopportunityforlearnerstopublishtheirwritings.Thedevelopmentofvirtualschoolmagazineswascarriedout in 4schoolsinDepokCity, namelySMP and MAMadinatulQuran, SMKBhaktiKarya,andMTs. Al-Ittihad.Theseactivitiesarecarriedoutbyutilizingtheissuudigitalplatform.Thepublicationoftheschool'svirtualmagazineiscarriedoutonceamonth.The school'svirtualmagazineismanaged by teachersandprovidedbytheschoolasaforumforstudentcreativity.Thewritingrubricsprovidedinthevirtualmagazinearepoetry, news, shortstories,andphotojournalism.Studentsinallfourschoolshavebeenabletopublish the firstissueoftheschool'svirtualmagazine.Each school has1(one)issuuaccountmanagedbyteachersastheirvirtualschoolmagazinepublishingplatformforfree.